Trailblazers : how top business leaders are accelerating results through inclusion and diversity - Anderson, Redia (Wiley ; John Wiley [distributor], 2010)
"To reap the full benefits of diversity and inclusion, today's forward thinking companies look past "diversity" training towards a more comprehensive, holistic business approach. These leaders incorporate diversity and inclusion into every aspect of business culture, employee engagement, talent management and market penetration. Trailblazers reveals the practices, metrics and research, as well as the anecdotal evidence, for building and sustaining workplace cultures that make strategic diversity and inclusion a business necessity. Focusing on concrete actions you can implement immediately, this insider guide profiles the best practices award-winning companies have used on a sustained basis to transform their organizations."--Resource description page.